PENGARUH MASA KERJA TERHADAP KINERJA KARYAWAN HOTEL NAGOYA PLASA BATAM - Tjiptojuwono, Eko (Nsc Press, 2019)
The Impact of Work Period toward The Performance of Employees of Nagoya Plasa Hotel Batam. The purpose of thisstudy is to determine the impact of work period on the performance of employees of Nagoya Plaza Hotel Batam. Theresearch was conducted on 96 employees by using saturated sample method which are employees of Hotel Nagoya PlasaBatam. Based on the results of the study note that the results of items validity test show all indicators are valid , reliabilitytest results indicate that all items reliable, results of adjusted R2 test shows 13.60% the value of the dependent variable isdetermined by the independent variable which means that 86.40% effected by outside factors , the result of Ftest show theregression model is fit to be used and show a significant influence simultaneously, the result of ttest show the work periodhave a significant and a positive impact on the performance of employees. The results of this study can be used asreference materials for hotel management in implementing employee performance improvement strategies.